The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.marpolbul.2014.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and biochemical stress responses of Palinurus elephas after exposure to boat noise pollution in tank

Abstract: This study examined the effects of boat noise on the behavioural and biochemical parameters of the Mediterranean spiny lobster (Palinurus elephas). The experiment was conducted in a tank equipped with a video and audio recording system. 18 experimental trials, assigned to boat noise and control conditions, were performed using lobsters in single and group of 4 specimens. After a 1h habituation period, we audio- and video-recorded the lobsters for 1h. During the experimental phase, the animals assigned to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 89 publications
(113 reference statements)
6
62
1
2
Order By: Relevance
“…Recently there have been reports in the literature that under acoustic stress, THC is persistently lowered, indicating that these practices may alter, at least temporarily, the number of circulating haemocytes (Celi et al 2013;Filiciotto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently there have been reports in the literature that under acoustic stress, THC is persistently lowered, indicating that these practices may alter, at least temporarily, the number of circulating haemocytes (Celi et al 2013;Filiciotto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that noise pollution upregulate Hsp70 protein expression in the red swamp crayfish (Procambarus clarkii (Girard, 1852)) and European spiny lobster (Palinurus elephas (Fabricius, 1787)) (Celi et al 2013;Filiciotto et al 2014). According to their molecular size, they are usually classified into the following families: Hsp100s, Hsp90s, Hsp70s, Hsp60s, Hsp40s, and small heat shock proteins (smHsps).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the creation of man-made structures, dredging, or the building of permanent structures can not only change the biotic and abiotic components of an ecosystem, but also the acoustic landscape that characterizes it, thus also altering its ecology. Indeed, during the course of these activities, large amounts of mechanical energy can be spread, contributing to: an increase in stress factors for aquaculture species, the displacement of wild species, or the estrangement of one or more species from protected areas (Wysocki et al, 2006;Borsani et al, 2008;Filiciotto et al, 2013;Firestone 2 and Jarvis 3, 2007;Mitson and Knudsen, 2003). Other physical perturbation, which can be connected to maritime shipping and underwater acoustic equipment, can interfere in a more or less significant manner with all the activities identified by Art.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory activities are used to assess qualitative and quantitative factors and the effects that pollution sources can have on species Filiciotto et al, 2014). It is widely documented that, above certain thresholds of intensity and frequency, anthropogenic noise is a real impact factor from a bio-ecological point of view (alteration of physiological, biochemical and behavioral parameters) by acting as a limiting factor for the ecosystem (Popper and Hawkins, 2012;Vasconcelos et al, 2007).…”
Section: About the Research: Support Activitiesmentioning
confidence: 99%
“…Respiration and oxygen con-sumption rates have been used as measures of direct physiological response in fish (Radford et al 2016), cephalopods (Kaifu et al 2007), and lobsters (Filiciotto et al 2014). As an example, European seabass exposed to playbacks of recordings of pile-driving and seismic surveys exhibited increased ventilation rates in relation to control individuals exposed to ambient-noise playback (Radford et al 2016).…”
Section: Sub-lethal Effectsmentioning
confidence: 99%